Income comparisons and non-cognitive skills - Santiago Budría; Ada Ferrer-i-Carbonell (Institute for the Study of Labor (IZA), 2012)
People gain utility from occupying a higher ranked position in the income distribution of the reference group. This paper investigates whether these gains depend on an individual's set of non-cognitive skills. Using the 2000-2008 waves of the German Socioeconomic Panel dataset (SOEP), a subjective question on Life Satisfaction, and three different sets of non-cognitive skills indicators, we find significant and robust differences across skills groups. People who are more neurotic, extravert and have low external locus of control and low negative reciprocity are more sensitive to their individual position in the economic ladder. By contrast, the Life Satisfaction reaction to changes in economic status is significantly lower among individuals who score high (low) in negative (positive) reciprocity, and are at the bottom of the distribution of neuroticism, extraversion. The heterogeneity on the importance of income comparisons needs to be taken into account when, for example, introducing them into economic models, predicting individuals' behaviour, or making welfare judgments.
urn:nbn:de:101:1-201207125514
Keywords: D62; I31; 330; life satisfaction; income comparisons; personality traits; Zufriedenheit; Einkommensverteilung; Sozialer Status; Nutzen; Persönlichkeitspsychologie; Schätzung; Deutschland